Bovine cysticercosis in the State of São Paulo, Brazil: Prevalence, risk factors and financial losses for farmers - Comin, Vinicius Cardoso; Mathias, Luis Antonio [UNESP]; Almeida, Henrique Meiroz de Souza [UNESP]; Rossi, Gabriel Augusto Marques (Elsevier, 2021)
Taenia saginata is the causative agent of bovine cysticercosis (BCC) and human taeniasis, two diseases that have economical and public health importance, respectively. This research focused on determining BCC prevalence in the state of São Paulo state, Brazil, in the period of 2017–2019, as well as associating risk factors related to disease occurrence and estimate the economic impact to beef producers. Data from 6,277,758 bovine carcasses originating from 571 municipalities and 15 different mesoregions in the state of São Paulo was gathered and analyzed. Cysticerci were detected in a total of 88,700 carcasses at meat inspection, resulting in an apparent prevalence of 1.41 % (C.I. 95 % 1.40–1.42 %). BCC was widespread in this state and its spatial distribution varied in municipalities and mesoregions. The variable number of milking cows in the municipality was significantly associated (OR = 1.48, p = 0.00) with BCC cases, conversely, the presence of peasant's settlements in the municipality was a protective factor (OR = 0.49, p = 0.02). Financial losses for cattle farmers were estimated at US$ 5,829,103.99. The results of this research show that there is still room for implementation of bovine cysticercosis control measures in endemic areas, aiming to reduce financial losses to farmers as well as reduction of human taeniasis cases in the population.
Keywords: Brazil; Cattle; Epidemiology; Meat inspection; Prevalence; Risk factors; Taenia saginata